الوكالة الوطنية لتطوير الاستثمار و دورها في تحفيز المقاولاتية حالة ولاية بشار - Benzaier, Mebarek; Benzaeir, Abdelouaheb (Finance and Business Economies Review, 2017)
Algeria has sought since independence to get out of the circle of the rentier economies and that by trying to activate the contributing sectors in the composition of Total output Outside hydrocarbons ; entrepreneurship and considered one of the tools relied upon in this regard ; And not as an option but as inevitability were produced by the internal and external economic transformations. And This paper aims to highlight the success of entrepreneurial support and accompany the bodies represented by the National Agency for Investment Development- province of Bechar-.